Masons in Italy: The Borderland Between Fanaticism and Liberty - Mola, Aldo (2013)
This article presents a survey through the history of Freemasonry in the current Italian territory, from its eighteenth-century origins to present, and analyzes the influence that the fraternity had on the country’s historical events. The article especially demystifies the legends surrounding the relationship between Freemasonry and the history of Italy.